Contribution to the taxonomic revision of Brachycorythis-complex (Orchidaceae, Orchidoideae) - Olędrzyńska, Natalia; Szlachetko, Dariusz Lucjan (Biodiversity: Research and Conservation, 2021)
The aim of this paper is to present materials towards the taxonomic revision of Brachycorythis-complex (Orchidinae, Orchidaceae), which constitutes seven terrestrial genera and forty-eight species distributed in sub-Saharan Africa, Madagascar and SW Asia. The detailed morphological descriptions, together with distribution data and ecological preferences for particular taxa are provided. Artificial keys for taxa identification were prepared. A molecular timescale for Brachycorythis species on a background of the subtribe Orchidinae was reconstructed using nuclear and plastid molecular markers. The results show that representatives of Brachycorythis separated from its last common ancestor presumably ca 20 Mya and the youngest taxa within the group seem to be its Asiatic representatives.